The Waxing and Waning of Western Influence: Construction of the Fengtian YMCA Staff Residence (1914–1926) - WU Zhihua, (Journal of Research for Christianity in China (JRCC), 2025)
The North American Association of the Young Men's Christian Association (YMCA) introduced the YMCA to China in 1895 and constructed numerous residences for Western staff members. Following its establishment in 1914, the Fengtian YMCA began surveying residential land under its first General Secretary, Yale Dun. Although the North American Association held the right to freely lease land in Fengtian City for permanent construction of YMCA residences under Article XIV of the 1903 Sino-American Treaty of Commerce and Navigation, Japan's land seizures in Northeast China sparked widespread local opposition to any foreign land leases or purchases. This fueled the rise of anti-Christian movements and rights restoration campaigns. Consequently, the Fengtian YMCA residences were only secured on a perpetual lease in the commercial district of Fengtian City on April 23, 1926, and were completed that December. Constructed using traditional local blue bricks, the three-story villa blended Chinese architectural elements within an overall Western modern style. This reflected its influence on the surrounding Chinese culture while also signifying the strengthening of Western civilization and the weakening of Western hegemony—a dynamic interplay of Western influence in various spheres. It heralded the birth of a progressive, independent, and self-reliant new China.